2015
DOI: 10.1103/physreve.91.042129
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of energy diffusion and local thermalization in nonequilibriumXXZspin chains with integrability breaking

Abstract: In this work we analyze the simultaneous emergence of diffusive energy transport and local thermalization in a nonequilibrium one-dimensional quantum system, as a result of integrability breaking. Specifically, we discuss the local properties of the steady state induced by thermal boundary driving in a XXZ spin chain with staggered magnetic field. By means of efficient large-scale matrix product simulations of the equation of motion of the system, we calculate its steady state in the long-time limit. We start … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 76 publications
2
64
0
Order By: Relevance
“…In the limit of no disorder (W = 0), we find that the energy current j E is independent of the length of the system, which signals that the energy transport is ballistic; this is consistent with previous work on the XYZ model [36]. Ballistic energy transport has been linked to the integrability of quantum systems [48], a characteristic which is also visible in the Poissonian statistics of the Hamiltonian's eigenenergy spectrum [49]. For 0 < ∆ ≤ 2 and 0 < η ≤ 1 we find that the average of r falls close to the Poissonian value r P = ln 4 − 1 over the entire spectrum.…”
Section: Fig 1 (A)supporting
confidence: 90%
“…In the limit of no disorder (W = 0), we find that the energy current j E is independent of the length of the system, which signals that the energy transport is ballistic; this is consistent with previous work on the XYZ model [36]. Ballistic energy transport has been linked to the integrability of quantum systems [48], a characteristic which is also visible in the Poissonian statistics of the Hamiltonian's eigenenergy spectrum [49]. For 0 < ∆ ≤ 2 and 0 < η ≤ 1 we find that the average of r falls close to the Poissonian value r P = ln 4 − 1 over the entire spectrum.…”
Section: Fig 1 (A)supporting
confidence: 90%
“…This suggestion has later received further support by the work [30], where an exact bound on the so-called Drude weight was derived for integrable systems driven by Lindblad operators. Numerical confirmations, although limited to XXZ spin chains, have also been found in [24,25] and the very recent [26]. Since a CFT is integrable, this would imply a non-negligible ballistic component even for non-integrable microscopic 1D systems if their low-temperature regimes were described by non-equilibrium CFTs.…”
Section: Resultsmentioning
confidence: 69%
“…2(a). We have run various tests using also the ρ T described in [23,25], and we found that using Eq. 11 was consistently resulting in ratios of effective inverse temperatures closest to 1.…”
Section: Discussionmentioning
confidence: 99%